Peace Education in Marginalized Communities in Nigeria: The 'Protect Our Future' Project - Edozie, Imoh (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
This paper explores the conflict in the Niger Delta area of Nigeria and the effect of the ‘Protect our Future’ Project. The conflict in the area has taken various dimensions. There have been various schools of thought on the reason for the continued spate of conflict, violence and recently now kidnapping in the Niger Delta. The most commonly held view is to attribute it to a potent cocktail of violence, underdevelopment, abject poverty in the area, lure for quick money, environmental damage and failure of government leading to a growing frustration and circle of violence among the people. However, in spite of the effort of the government and various stakeholders, the situation does not seem to be abating. This paper analyses the situation and proffers likely solutions to this age-long problem in the region that have taken a new dimension. These include the contribution of funds by persons who benefit from the community to a central fund to be used for education of members of the community. It finally reflects on the role the ‘Protect our Future’ Peace project is contributing and likely to contribute to the process of achieving peace in the Niger Delta.